Pembinaan Masyarakat Tentang Pencegahan Penyakit Tuberkulosis Di Desa Sampali Kecamatan Percut Sei Tuan - Nixson Manurung (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2022)
Tuberculosis (TB) is currently still a public health problem both in Indonesia and internationally and is one of the goals of sustainable health development (SDGs). TB is one of the top 10 causes of death and the primary cause of infectious agents in the world. The prevalence of tuberculosis sufferers in 2020 was 929 patients who took regular medication for less than 6 months, amounting to 48.87%. Some of the influencing factors are behavioral factors, namely knowledge, attitudes and behavior in the implementation of routine medication adherence. The method used is descriptive observational with 30 participants who are the people of Sampali Village, Percut Sei Tuan District. The PkM team provided the material in question 1) Definition of tuberculosis, 2) Causes of tuberculosis 3) Signs and symptoms of tuberculosis, 4) Complications of tuberculosis, and 5) Prevention of tuberculosis. 1) The majority of tuberculosis (TB) is bad in 28 people, 2) The causes of tuberculosis (TB) are mostly bad in 28 people, 3) Signs and symptoms of tuberculosis (TB) are mostly bad in 28 people, 4) Complications of tuberculosis ( TB) the majority of all participants did not know as many as 30 people and 5) correct prevention of tuberculosis (TBC) all participants could not afford as many as 30 people while after the implementation of the activity: 1) Definition of tuberculosis (TB) the majority was good as many as 28 people, 2) Causes of tuberculosis (TBC) the majority were good, 26 people, 3) Signs and symptoms of tuberculosis (TB), the majority were good, 28 people, 4) Complications of tuberculosis (TBC), the majority were good, 18 people, and 5) Prevention of transmission of tuberculosis (TB) was correct throughout participants have been able to as many as 26 people. Increased knowledge and skills of participants because the community has a great desire to treat and prevent dengue fever in family members at home.